2013
DOI: 10.1016/j.crci.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally friendly synthesis of 2-aryl-2,3-dihydroquinazolin-4(1H)-ones by novel Co-CNTs as recoverable catalysts

Abstract: The objective of this study is to investigate the possibility of using Co-CNTs as a green reaction medium and a catalyst for the cyclo-condensation of o-aminobenzamide with various aldehydes. This inexpensive, non-toxic, and readily available catalyst efficiently catalyzes the above condensation for the synthesis of 2-aryl-2,3-dihydroquinazolin-4(1H)-ones. Compared to the classical reaction, this is a simple, highly yielding, time saving, and environmentally friendly method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…We feel that this protocol is a valuable addition to the currently reported ones. [20][21][22][23][24][25] …”
Section: One-pot Synthesis Of 23-dihydroquinazolin-4(1h)-ones Under mentioning
confidence: 98%
See 2 more Smart Citations
“…We feel that this protocol is a valuable addition to the currently reported ones. [20][21][22][23][24][25] …”
Section: One-pot Synthesis Of 23-dihydroquinazolin-4(1h)-ones Under mentioning
confidence: 98%
“…26 All of these reactions are successful in producing the target compound although certain drawbacks, such as use of harmful solvents, expensive catalysts, and low yields, are associated with some of them. With the goal of making some of the above-mentioned methods benign, the reactions were carried out under solvent-free conditions 16,20,21 , using MW-irradiation 21,22 and of water 18,22,24,25 or ethanol 11,12,17,22 as solvents. However, none of them proceeded without the use of catalyst.…”
Section: One-pot Synthesis Of 23-dihydroquinazolin-4(1h)-ones Under mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] 2, 3-dihydroquinazoline-4(1H)-one and polyhydroquinoline structural motifs have been known to possess diverse biological activities such as antitumor, anticancer, antibiotic, antidiabetic, antibacterial, antidefibrillatory, antipyretic, and anticonvulsant agents. [22][23][24][25][26][27][28][29][30] Polyhydroquinolines also are well-known drugs for the treatment of cardiovascular and Alzheimer's diseases. [31,32] Furthermore, polyhydroquinoline derivatives are well-known as Ca 2+ channel blockers and drugs of NADH co-enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Besides, 2, 3-dihydroquinazoline-4(1H)-one derivatives can act as key structural motifs to design the new category of highly valuable synthetic drug candidates owing to their important pharmacological properties. [15,16] Recent literature studies clearly shown that a variety of molecules containing 2, 3-dihydroquinazoline-4(1H)-one structural units exhibit a series of significant biological activities such as antitumor, anticancer, antibiotic, antibacterial, antidefibrillatory, antipyretic, and anticonvulsant [17][18][19] The condensation of aryl, alkyl and hetroaryl aldehydes or ketones with anthranil amide in the presence of acidic catalysts is a well-known approach for the synthesis of 2, 3-dihydroquinazoline-4(1H)-ones. [20] In recent times, a variety of catalysts and promoter or reagents for the synthesis of these compounds have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%